2017
DOI: 10.1038/s41598-017-11535-z
|View full text |Cite
|
Sign up to set email alerts
|

Iron oxide nanoparticles can cross plasma membranes

Abstract: Iron deficiency is a major global public health problem despite decades of efforts with iron supplementation and fortification. The issue lies on the poor tolerability of the standard of care soluble iron salts, leading to non-compliance and ineffective correction of iron-deficiency anaemia. Iron nanoformulations have been proposed to fortify food and feed to address these issues. Since it was just postulated that some nanoparticles (NPs) might cross the plasma membrane also by a non-endocytotic pathway gainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 52 publications
2
28
0
Order By: Relevance
“…Iron fortification, in recent years, could be done by introducing iron and iron oxide nanoparticles in foodstuffs. Due to no change in character of fortified food, product stability and large bioavailability, they could also impart good health by increasing haemoglobin levels and nutrition [3][4][5][6]. Ice cream was enriched with alginate nanoparticles including Fe and Zn salts [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron fortification, in recent years, could be done by introducing iron and iron oxide nanoparticles in foodstuffs. Due to no change in character of fortified food, product stability and large bioavailability, they could also impart good health by increasing haemoglobin levels and nutrition [3][4][5][6]. Ice cream was enriched with alginate nanoparticles including Fe and Zn salts [7].…”
Section: Introductionmentioning
confidence: 99%
“…In sausages, iron was fortified as iron oxide nanoparticles in the form of colorants; in USA, for people preferring packed foods consumed around 450 µg/ day [8]. Recent reports have revealed that food fortified using iron nanoparticles were safe through in vivo and invitro experiments [6].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles (NPs), including ferritin or ferritin-mimicking molecules [93], appear promising, and devoid of unwanted effects. Noteworthy, a very recent and elegant study has demonstrated that iron-containing NPs cross the cell membrane by DMT1-independent mechanisms, like endocytosis, or even by a non-endocytotic pathway allowing direct access to the cytoplasm [94].…”
Section: New Preparationsmentioning
confidence: 99%
“…This model is also promising for studying NP diffusion across the intestine. Indeed, paracellular pathway, endocytosis-exocytosis, M-cell-mediated pathway (Yu et al 2016) as well as simple diffusion by direct crossing of the plasma membrane (Zanella et al 2017) are the mechanisms by which NPs are supposed to cross the intestinal biological barrier.…”
Section: Introductionmentioning
confidence: 99%